Dye degradation of spherical and rod-shaped CuO semiconductor nanoparticles. Issue 1 (15th May 2017) - Singh, Gurjinder; Panday, Sudhakar; Rawat, Mohit; Basu, Soumen
Abstract : The chemical and physical properties of nanoparticles (NPs) are highly dependent on size, shape and structure. The smaller size of copper oxide (CuO) NPs paves the way for applications in sensor technology, solar cells, biology and photocatalysis. Here the authors report a wet chemical method for synthesis of stable CuO NPs by using copper acetate as the precursor and the cationic surfactant cetyltrimethylammonium bromide or hexadecyltrimethylammonium bromide (Ctab) ([(C16 H33 )N(CH3 )3 ]Br). Ultraviolet (UV) spectroscopy shows that the CuO NPs have an absorbance peak at 289 nm, which gives a band gap of 2·5 eV, and Fourier transform infrared spectra confirm the capping of Ctab. Scanning electron microscopy images show that the NPs are spherical and rod-shaped and have diameters varying between 9 nm and 1 μm. The X-ray diffraction pattern shows that the synthesised NPs were high-purity CuO with average size = 10 nm, which is also confirmed by transmission electron microscopy results. The as-synthesised CuO NPs were subjected to a dye degradation study in time-specific mode on methyl orange (MO) and Congo red (CR) dyes by using a UV-irradiated source. The calculated degradation efficiencies of approximately 92% (MO) and 91% (CR) show promising application of CuO NPs in photocatalytic activity.